(untitled) (Journal of the Bangladesh Agricultural University, 2024)
This study identified the problems associated with the design, construction, operation, and maintenance of risers in buried pipe irrigation systems and proposed a modified design. The problems of buried pipe irrigation systems were assessed by inspecting three deep tube wells (DTWs) supplying water through buried pipes with twenty-five outlets. One DTW of the Bangladesh Agricultural Development Corporation (BADC) with five outlets in Netrokona, and one with fifteen outlets in Bara Kailati village and one with five outlets in Bali Bazar, both in Netrokona Sadar, were selected. Data were collected from farmers, field staff, and management authorities by employing pretested questionnaires and field investigations. Site visits revealed that the primary problems were the water leakage through outlets and cracks in the riser structure around the outlet. These problems were due to unsuitable outlet design of the buried pipe system. To overcome these problems, the riser design has been modified structurally, that may lead the buried pipe to suitable and durable performance of buried pipe irrigation system and reduce water losses. J Bangladesh Agril Univ 22(2):225-230, 2024